Advances in organic solar cells: Materials, progress, challenges and amelioration for sustainable future - Jain A.; Kothari R.; Tyagi V.V.; Kumar Rajamony R.; Shakeel Ahmad M.; Mohan Singh H.; Raina S.; Pandey A.K. (Elsevier Ltd, 2025)
The erratic outlay of energy, due to a variety of reasons ranging from geopolitical impediments to global monetary matters, can be witnessed to make efforts toward the vicissitude of a clean energy society. Organic solar cells (OSCs) present many appealing prospects and have the potential to realize this transition with their co-occurring technologies. The augmentation in their efficiency is essential for their triumphant commercialization. Regardless, researchers in this domain have made stringent steps to demonstrate > 15 % efficiency, recently achieving nearly 20 %. The doorway of Non-Fullerene Acceptors (NFAs) has fetched a reinvigorated age in the blossoming of OSCs. In this review, we have given an insight of OSCs and recent advancements in the field to discern the materials exemplified in the literature. Novel device architectures such as ternary and tandem, trustworthy for high efficiency, have been elucidated. The fabrication techniques and performance of some efficient large-scale devices (>1 cm2) are reviewed. The pivotal challenges confronting OSCs and some amelioration strategies to create a paradigm shift in further achieving state-of-the-art OSCs are also enlisted in the present review. ? 2024 Elsevier Ltd